Regulasi Hukum Kontrak Pada Pekerjaan Konstruksi Yang Mengakibatkan Kerugian Keuangan Negara - Nurhimmi Falahiyati; Sahbudi Sahbudi; Aswan Halomoan Lubis (Mahesa Research Center, 2024)
Abuse in construction work auctioned by the government or being a partner of the government is one form of criminal offense that harms the state. This research uses a legal approach with a focus on Law Number 18 of 1999 concerning Construction Services. This study found that the law is still lacking in providing legal certainty and meeting the development needs of the implementation of construction services. Changes in regulations or requirements in the selection document for the procurement of goods/services are needed that have a major effect on the implementation of work, so that termination of the contract can have a detrimental impact on the state. The importance of provisions and legal certainty regarding regulations in the termination of construction work contracts is so that there is no overlap or difference in perception in interpreting the rules regarding the disbursement of implementation guarantees. This research highlights the importance of clear legal regulation in regulating construction work contracts to prevent state financial losses.